2013
DOI: 10.1121/1.4805555
|View full text |Cite
|
Sign up to set email alerts
|

Detectability study of warning signals in urban background noises: A first step for designing the sound of electric vehicles

Abstract: Session 2aNSa: Transportation Noise 2aNSa4. Detectability study of warning signals in urban background noises: A first step for designing the sound of electric vehicles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several studies have proposed or compared different warning signal in terms of detection (Parizet et al, 2013; Robart, Parizet, Garcia, 2012; Voigt et al, 2011) one of them proposing a cross cultural experiments between German and Japanese subject (Yamauchi et al, 2012). Moreover in a study of Misdariis et al (2013) on the detection of several warning signals it was found out that reaction times are significantly and predominantly decreasing along the course of the experience (several days), meaning that a learning effect occurs.…”
Section: Ings Are Expected Introducing Lighter Vehicles (Olev 2013)mentioning
confidence: 99%
“…Several studies have proposed or compared different warning signal in terms of detection (Parizet et al, 2013; Robart, Parizet, Garcia, 2012; Voigt et al, 2011) one of them proposing a cross cultural experiments between German and Japanese subject (Yamauchi et al, 2012). Moreover in a study of Misdariis et al (2013) on the detection of several warning signals it was found out that reaction times are significantly and predominantly decreasing along the course of the experience (several days), meaning that a learning effect occurs.…”
Section: Ings Are Expected Introducing Lighter Vehicles (Olev 2013)mentioning
confidence: 99%
“…The scenario chosen for the test corresponds to the following situation (Misdariis et al, 2013): a pedestrian located on the sidewalk of a street waits before crossing. An EV may pass by, coming either from the right or from the left.…”
Section: Scenariomentioning
confidence: 99%
“…To obtain a pseudo-realistic passing-by scenario, the following properties have been implemented:  The sound level of the EV is modulated according to the vehicle/listener distance. The model used, based on acoustic theory, considers the EV as a monopole and provides a sound level inversely proportional to the distance to the listener (1/r) (see Figure 1) (Misdariis et al, 2013), (Lee et al, 2017),  The speed of the EV is considered as constant and equal to 20km/h,  The duration of the sound stimuli is 15 seconds,  The Doppler effect (shifting in frequency due to the speed of the source) is taken into account for a more realistic experience,  The direction of the car (from the right or from the left) is randomly chosen,  The panning of the EV sound is managed in such a way that the source goes progressively from one canal (left or right, depending of the direction of the EV) to the other (right or left) according to the position of the vehicle.…”
Section: Scenariomentioning
confidence: 99%
See 1 more Smart Citation